Harmonization of Fiqh with E-commerce: a Review - Khoerulloha, Abd. Kholik; Mesh’al, Fairuz; Ridwan, Ahmad (AFEBI Islamic Finance and Economic Review, 2023)
Transactions in e-commerce are increasing massively, this happens because e-commerce platforms present a variety of features that are very relevant to the needs of users, making it easier to transact according to user preferences. However, for Muslims, it is important to be careful because not all transactions that occur in e-commerce comply with sharia principles. The purpose of this research is to provide an understanding for Muslims regarding the contracts used in conducting transactions in e-commerce in accordance with sharia principles. This research uses a qualitative research method with a normative juridical approach that examines the legal aspects of e-commerce based transactions within the framework of transaction law in Islamic economics. The results show that several contracts that can be used by Muslims as a basis for legitimising transactions, namely: wadi'ah yad dhamanah, salam, murabahah bi al-wakalah, ijarah and khiyar. These agreements will be an instrument for Muslims in conducting transactions in e-commerce that are in accordance with sharia principles. This research can also provide guidance to businesses and e-commerce platforms to better understand the legal requirements in transactions with sharia-based consumers. Thus, it can create a more inclusive and shariah-compliant business environment, which in turn can open up greater business opportunities in the Muslim market. Keywords: e-Commerce, Fiqh, Aqd.